Pirmasis Lietuvoje ekslibrisų konkursas - (:unkn) unknown (My University, 2004)
On the 8th of November, 1908 T. Wróblewski, an activist of culture and comunity of Vilnius district, celebrated his 50th anniversary. The golden anniversary of the bibliofile was commemorated by the first contest of ex-librises in Lithuania. The names of the participants of the contest were unknown. Some of the works were marked by pseudonims. Adam Jerzy Półtawski (1881, Warsaw - 1952, Cracow) won the contest. This prominent person, honoured for his Polish press and culture activities, was an excellent master of graphics, a creator of Polish founts and an illustrator of books. Now one can often come across A. Półtawski ex-librises in the books which belonged to T. Wróblewski.
The first contest of ex-librises in Lithuania
Skyriaus antraštė: Iš bibliotekos praeities: Tadas Vrublevskis ir jo biblioteka